Ultrasonic assisted membrane anaerobic system (UMAS) - Nurulasma, Zainudin (2013)
The direct discharge of Palm oil mill effluent (POME) wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), Total suspended solids (TSS) and biochemical oxygen demand (BOD). Traditional ways for POME treatment have both economical and environmental disadvantages. In this study, ultrasonic assisted-membrane anaerobic system (UMAS) was designed used as an alternative, cost effective method for treating Palm oil mill effluent (POME) wastewater. This system has a value proposition and advantage in market segmentation. Through the market strategies and financial analysis, the future market of the system can be easily to penetrate. Six steady states were attained as a part of a kinetic study that considered concentration ranges of 12,960 to 25,600 mg/l for mixed liquor suspended solids (MLSS) and 10,091 to 22,528 mg/l for mixed liquor volatile suspended solids (MLVSS). Kinetic equations from Monod, Contois and Chen & Hashimoto were employed to describe the kinetics of POME treatment at organic loading rates ranging from 0.5 to 9.5 kg COD/m3/d. Throughout the experiment, the removal efficiency of COD was from 96.6 to 98.5% with hydraulic retention time, HRT from 480.3 to 5.4 days. The growth yield coefficient, Y was found to be 0.58gVSS/g COD the specific microorganism decay rate was 0.21 d-1 and the methane gas yield production rate was between 0.27 l/g COD/d and 0.59 l/g COD/d. Steady state influent COD concentrations increased from 67,000 mg/l in the first steady state to 91,400 mg/l in the sixth steady state. The minimum solids retention time, min c which was obtained from the three kinetic models ranged from 6 to 15.6 days. The k values were in the range of 0.360.525 g COD/ g VSS. d and max  values were between 0.28 and 0.377 d-1. The solids retention time (SRT) decreased from 860 days to 10.6 days. The complete treatment reduced the COD content to 3000 mg/l equivalent to a reduction of 98.6% reduction from the original.